Evaluación de la calidad nutricional de diferentes formulaciones a base de las harinas de trigo (triticum aestivum), quinua (chenopodium quínoa) y oca (oxalis tuberosa) y su utilización en la elaboración de panecillos - Borja Monar, Edgar Gustavo (2018)
This research was developed at the State University of Bolivar, Faculty of Agricultural Sciences, Natural Resources and the Environment, Agroindustrial Engineering Career, Agroindustrial Complex. Its general objective was to evaluate the nutritional quality of different formulations based on wheat flours (triticum aestivum), quinoa (chenopodium quinoa) and oca (oxalis tuberosa) and their use in the preparation of bread rolls. A completely randomized block design A x B (DBCA) with two replications was applied to the mixtures of wheat, quinoa and oca flours, and was also applied in the sensory analysis to determine the best treatment, which was based on the Tukey test at 5% to compare averages of treatments. Statistical analysis was used the program (Infostat-Version 2017). The substitution percentages of wheat flour were 5, 10 and 15%, both for quinoa flour and for goose meal. The physical-chemical analysis of the mixture of flours (moisture, ash, carbohydrates, protein and fiber) was carried out. Increases in the percentage were observed as the level of substitution of wheat flour by quinoa flour increased. and oca. In the dough the gluten strength was determined, changes were observed during the kneading process, appreciating elasticity losses due to the partial replacement of the wheat flour. While the physical-chemical characteristics (moisture, ash, protein and fiber), microbiological (total coliforms, E. coli, molds and yeasts) were determined in the finished product, they showed values <10, so the product did not present any type of any contamination. The panel of tasters on a scale of 1 - 5 points, provided an assessment of good (3) to treatment T6. The cost / benefit relation to the T6 treatment was determined with the code A2B3C1 (10% oca flour, 15% quinoa flour and 75% wheat flour) it was determined that the total production cost for the preparation of the best treatment is $ 5.58, having the cost benefit ratio $ 1.42, that is, for every $ 1.00 invested, a profit of 42 cents will be obtained.